Disparities and dynamics in evaluating inter-district agricultural development in Uttar Pradesh - Tariq Mahmood Usmani,; Ahmad Mujtaba Siddiqui,; Md. Babor Ali, (National Geographical Journal of India, 2025)
This study conducts a spatial analysis of inter-district agricultural development in Uttar Pradesh, India, using key indicators such as net sown area, cropping intensity, irrigation intensity, canal length per 1,000 hectares of net sown area, fertilizer consumption, and net sown area per cultivator. The findings reveal significant spatial disparities, with Western Uttar Pradesh demonstrating higher levels of irrigation coverage and fertilizer consumption, largely attributed to historical agricultural advancements, particularly those initiated during the post-Green Revolution. In contrast, regions like Bundelkhand demonstrate lower agricultural performance, primarily due to limited irrigation infrastructure and challenging agro-climatic conditions. The study highlights that agricultural development in Uttar Pradesh is not uniform and is influenced by a complex interplay of physical, infrastructural, and institutional factors. The use of comparative indicators facilitates a deeper understanding of the developmental imbalances at the regional level. These disparities emphasize the need for targeted, region-specific policy interventions to enhance resource utilization and productivity in lagging areas. The study underscores the importance of integrating spatial analysis into agricultural planning to support equitable and sustainable rural development. The findings offer valuable insights for policymakers, planners, and researchers aiming to design inclusive strategies that bridge development gaps and promote agricultural resilience across diverse districts of Uttar Pradesh.